(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Cleft palate is a congenital malformation in the maxillofacial region that separates the palatal structure including the palatine bone, the palatine levator muscle mass, the pharyngeal stretcher muscle, and the mucosa. Cleft palate, although not life-threatening, causes difficulties in eating and communicating. In the treatment of Cleft palate, it is necessary to have a comprehensive treatment plan from birth to adulthood with the coordination of many specialties. Up to now, there is no research topic on cleft palate treatment in Quang Ngai. Objectives: To describe the clinical characteristics of patients with Cleft palate treated at Quang Ngai Hospital for women and childern and evaluate the results of cleft palate surgery in the study subjects. Methods: A descriptive, prospective and longitudinal clinical study was performed on 32 patients with congenital cleft palate who were examined and treated surgically at Quang Ngai Hospital for women and childern from April 2020 to September 9 2021. Results: Clinical characteristics: Research results on 32 patients with cleft palate show that total cleft palate must account for the highest percentage (40.6%), 62.5% cleft palate combined with cleft lip. The reason for admission to hospital due to slurred speech accounted for the highest rate. There are 40.6% of patients with more than 2 tooth decay. The width of the cleft palate at the position of the posterior nasal spikes averaged 16.1±3.4mm. The mean preoperative soft arch length was 20.84±3.44mm; after surgery was 29.13±3.24mm, increased by 39.78%. Surgical results: There were no cases of postoperative wound infection. Patients discharged from hospital with good incisions reached 96.6%. Initial results of cleft palate treatment were very positive, after 2 months of re-examination, good incision accounted for 90.6%; 9.45% of patients have stoma. Conclusions: The results of Cleft palate treatment at the Hospital of Obstetrics and Gynecology in Quang Ngai province initially achieved very positive results, after 2 months of re-examination, the incision was good, accounting for 90.6%; 9.45% of patients have stoma.